A matemática moderna no ensino primário gaúcho (1960-1978): uma análise das coleções de livros didáticos Estrada Iluminada e Nossa Terra Nossa Gente - Alves, Antônio Maurício Medeiros (2013)
The core thesis developed by this study is that the global movement of renewal in the teaching of mathematics, known as the Modern Mathematics Movement (MMM), has established itself in the state of Rio Grande do Sul in a heterogeneous fashion, due to a set of actions orchestrated by different subjects in different teaching/teacher s education/research institutions. Such movement has influenced the local didactic production, leading to the reformulation of the collection entitled Estrada Iluminada ( Lighted Path ) which, under the new title Nossa Terra Nossa Gente ( Our Land Our People ), introduces the Modern Mathematics under the strong influence of the studies of the Hungarian mathematician Zoltan Paul Dienes. The MMM was originated in the mid 1960s, a period that was marked worldwide and in Brazil as well, by important discussions about the necessary renewal of mathematics teaching. In Rio Grande do Sul, however, there had already been a concern with teacher s education since the 1950s, thanks to studies in the field of cognitive psychology, mainly represented by Jean Piaget. The debate has involved different subjects connected to different institutions, such as Normal Schools, Universities, the Center for Educational Orientation and Research (CPOE) and the Porto Alegre Study Group on Mathematics Teaching (GEEMPA). These subjects included in their discussions topics of Modern Mathematics as, for instance, Set Theory, this discussion contributed to the debate about mathematics teaching modernization in RS, as well as the formation of teachers, especially who worked in Primary Education. In the same period there was, statewide, a process of professionalization of/in the didactic production, and textbooks for primary teaching started to be produced by CPOE Educational Technicians and Primary Advisers between the years of 1950 and 1980. In that context, we highlight the production of teachers Cecy Cordeiro Thofehrn and Nelly Cunha, authors of the didactic books made object and main source of study in this research: Estrada Iluminada and Nossa Terra Nossa Gente . Fifty-two copies from both these collections have been gathered, which were reduced to 17 volumes after a process of horizontal analysis. The data were built after vertical analysis, and interpreted considering four principles (categories) identified through the reading of the MMM works of reference: Set Theory; arithmetic operations; study of relationships; and topological structures. This way, by the analysis of the books under focus, it was possible to identify which Modern Mathematics contents have been included in the reformulation of said collections. Besides the didactic books other sources, such as legislation, works of reference authors on MMM and different academic works about the movement have also contributed for this study. With its results, the study intends to contribute to the field of History of Mathematical Education, of School Subjects and of Didactic Books.